MUHAMMAD ZAINAL ABIDIN, 2025. THE DEVELOPMENT OF VERB CONJUGATION IN THE TEXTBOOK "THEORETICAL FOUNDATIONS OF NAHWU AND SHARF" THROUGH THE APPLICATION OF THE AL-BIDAYAH METHOD TO STUDENTS AT AL-BIDAYAH ISLAMIC INSTITUTE IN TEGAL PASAR KLIWATS JEMBER - Muhammad Zainal Abidin; Abdul Haris; Maskud (International Journal of Teaching and Learning, 2025)
This study aims to identify and describe the development and validity of effective drainage materials. The researchers used a research and development (R&D) method using the ADDIE model that produces new products. The sample of this study was students in the special education class of Tegal Besar Kliwatis Jember. The teaching material developed was the book “Basic Theory of the Beginner Level Albidayah Method” by Abdul Haris which then produced a new product in the form of a book “Sharf Science Dialogue (Tasrif Lughawi & Istilahi)” with the application of questions and answers between teachers and students. Then to collect the required data, researchers used observation, interviews, and documents for qualitative data. From this study, two results were obtained (1) The product validity value obtained from the teaching material expert was 94% and from the media expert was 94%, which indicates that the learning method using question and answer by the teacher-student is feasible to use. (2) The level of effectiveness is calculated using pre-test and post-test with t-test analysis.  The result obtained is 10.215 and this result is more than t0.025;9 which means H0 is rejected. This shows that there is a significant effect before and after using the product to teach and apply morphology.